ANALYSIS OF MAQASHID AL-SYARI‘AH ON THE PRACTICE OF WOMEN AS SUPREME COURT JUSTICES - Muhammad Afif Al Husen; Ahmad Very; Kurniati Kurniati (Makkah: Journal Of Islamic Studies, 2026)
The This study aims to analyze the maqashid al-shari'ah (the principles of Islamic jurisprudence) in relation to the practice of women as supreme court judges in Muslim countries by comparing the judicial systems of Indonesia, Egypt, and Morocco. The methodology used in this study is library research, with data collection conducted by reviewing and examining several journals and articles related to the issues raised in the study. The collected data were then analyzed descriptively. The results of the study indicate that the learning process has a significant influence in improving (1) the maqashid al-shari'ah as the basis for women's permissibility to act as judges with an orientation towards justice and welfare (2) the practices of female judges in Indonesia, Egypt, and Morocco differ according to the legal and social context of each country (3) a comparative assessment from the perspective of maqashid al-shari'ah confirms that these differences in practice remain in line with the objectives of Islamic jurisprudence as long as they are based on competence, integrity, and a real contribution to improving the quality of justice. Based on the research results, it can be concluded that the role of women as supreme court judges in Indonesia, Egypt, and Morocco aligns with the Maqasid al-Shari'ah (Islamic principles) because it emphasizes justice and public welfare based on competence and integrity.